2011
DOI: 10.1007/s10964-011-9667-1
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Timing and Substance Use in Middle Adolescence: A 2-Year Follow-up Study

Abstract: Earlier research has associated early puberty with emotional and behavioral symptoms particularly among girls, while among boys, findings have been contradictory as to whether risks are associated with early or late pubertal timing. We studied the association between pubertal timing and substance use behaviors in middle adolescence in a 2-year follow up study of 2,070 (mean age 15.5 years, SD 0.36; 56.4% females) Finnish adolescents. Pubertal timing was measured by age at menarche/oigarche. Eleven years or les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 40 publications
7
76
3
2
Order By: Relevance
“…In boys, found that early maturation in 7th grade predicted more externalizing symptoms in 8th, 9th, and 10th grades; perceived early timing also predicted delinquency in boys and girls across several grades (Lynne et al, 2007 ). One study found enduring effects of early puberty on substance use across two years in boys but only temporary effects in girls (Kaltiala-Heino et al, 2011 ), whereas another found only temporary effects of early and late maturation in boys (Andersson & Magnusson, 1990 ). The few long-term follow-up studies document weak to no lasting effects of early maturation on externalizing psychopathology in adulthood (Magnusson et al, 1985 ;Stattin & Magnusson, 1990 ) although one study found that perceived late maturation in boys predicted lifetime disruptive behavior and current substance use disorders in early adulthood (Graber et al, 2004 ).…”
Section: Distinguishing Short Versus Long-term Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In boys, found that early maturation in 7th grade predicted more externalizing symptoms in 8th, 9th, and 10th grades; perceived early timing also predicted delinquency in boys and girls across several grades (Lynne et al, 2007 ). One study found enduring effects of early puberty on substance use across two years in boys but only temporary effects in girls (Kaltiala-Heino et al, 2011 ), whereas another found only temporary effects of early and late maturation in boys (Andersson & Magnusson, 1990 ). The few long-term follow-up studies document weak to no lasting effects of early maturation on externalizing psychopathology in adulthood (Magnusson et al, 1985 ;Stattin & Magnusson, 1990 ) although one study found that perceived late maturation in boys predicted lifetime disruptive behavior and current substance use disorders in early adulthood (Graber et al, 2004 ).…”
Section: Distinguishing Short Versus Long-term Pathwaysmentioning
confidence: 99%
“…Compared to their on-time-and late-maturing peers, early-maturing girls and boys show elevated levels of aggression and antisocial behavior, such as oppositional defi ant and conduct disorder symptoms, truancy, theft, vandalism, and bullying (Caspi & Moffi tt, 1991 ;Felson & Haynie, 2002 ;Flannery et al, 1993 ;Ge, Brody, Conger, Simons, & Murry, 2002 ;Graber et al, 1997 ;Kaltiala-Heino, Marttunen, Rantanen & Rimpela, 2003 ;Lynne, Graber, Nichols, BrooksGunn & Botvin, 2007 ;Magnusson et al, 1985 ;Storvall & Wichstrom, 2002 ;Susman et al, 2007 ) as well as risky and norm-breaking behavior, including smoking and earlier and more frequent sexual activity (Flannery et al, 1993 ;Magnusson et al, 1985 ). Both early-maturing boys and girls also engage in earlier and higher rates of alcohol and substance use/abuse (Kaltiala-Heino, Koivisto, Marttunen, & Sari, 2011 ;Schelleman-Offermans, Knibbe, Engels, & Burk, 2011 ;Stice et al, 2001 ), whereas latematuring boys engage in lower rates of substance use (Graber et al, 1997 ). In one study, faster pubertal tempo predicted more externalizing symptoms in girls but only inconsistently predicted externalizing symptoms in boys (Marceau et al, 2011 ).…”
Section: Externalizing Psychopathologymentioning
confidence: 99%
“…Moreover, a study of youths in Finland reported that an early age of first ejaculation was associated with earlier first experience of alcohol consumption, higher volume and frequency of alcohol consumption, and a higher risk of smoking and illegal substance use 3) . Various hypotheses have been suggested to explain why early puberty onset acts as a risk factor for substance use 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who experience early puberty are reported to show increased alcohol consumption 1) , smoking 2) , substance use 3) , and risky sexual behaviors 2) . There is an association between rapid physical maturity and violence, crime, illegal substance use, and early sexual intercourse 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Of course, such evolutionary-based influences are complex and interact with and are shaped by proximal environmental and cultural factors (Ellis, McFadyen-Ketchum, Dodge, Pettit, & Bates, 1999;Ellis, Shirtcliff, Boyce, Deardorff, & Essex, 2011). Del Giudice's (this issue) current use of evolutionary developmental theory, specifically life history theory, to provide a framework by which to organize and classify psychopathology is thus commendable in that fast versus slow life history strategies seems to have utility for explaining the developmental timing and onset of at least some types of psychopathology (e.g., substance abuse; Kaltiala-Heino et al, 2011;Lynne-Landsman et al, 2010;Negriff & Trickett, 2012). Further, a fast versus slow life history strategy may influence the development of particular types of traits that, in extreme form and perhaps particularly in certain contexts, may increase risk for specific clinical disorders.…”
Section: Application Of An Integrated Evolutionary Psychological Frammentioning
confidence: 99%